Disparitas Hasil Pembangunan Kabupaten/Kota Sebelum dan Sesudah Otonomi Daerah - Ahmad, Irdam (Jurnal Ilmu Administrasi Negara, 2013)
Since 2001, Indonesia has implemented decentralization based on Act No. 22 on LocalGovernment. This article aims to evaluate the impact of decentralization on districts developmentwithin the province of Yogyakarta, before and after decentralization, using Taksonomic Method,by computing pattern of development and measurement of development (mod) in each district,using city of Yogyakarta as benchmarking. Data used in this study are; (1) Gross Regional Domes-tic Product (GRDP) individual income, (2) share of GRDP in each district to GRDP at provincial level,(3) share of manufacturing sector to GRDP, (4) local own income, (5) literacy of population of 10-44years of age, (6) expectation of life at birth, (7) labor force participation rate, (8) gross enrollmentratio of 16-18 years of age, (9) percentage of household that have electricity. Source of all data arefrom BPS head office, province and district offices. The results shows that the measurement ofdevelopment in districts Sleman, Kulon Progo and Gunung Kidul are not difference, both beforeand after decentralization. In Bantul, the development process after decentralization is tend tobecome worse, while Gunung Kidul has the biggest mod, and categorized as under developingdistrict, either before or after decentralization. In addition, the results of this research also exactlythe same with Human Development Index (HDI), which means that Taksonomic Method can beused as new paradigm to evaluate the development process of a district/municipality to find out theimpact of decentralization policy, which has been lasting for ten years.